2010
DOI: 10.1128/jvi.01757-09
|View full text |Cite
|
Sign up to set email alerts
|

Rotaviruses Associate with Cellular Lipid Droplet Components To Replicate in Viroplasms, and Compounds Disrupting or Blocking Lipid Droplets Inhibit Viroplasm Formation and Viral Replication

Abstract: Rotaviruses are a major cause of acute gastroenteritis in infants and young children, producing a high burden of disease worldwide and over 600,000 deaths per annum, mainly in developing countries (43). Recently, two live attenuated rotavirus vaccines (49, 58) have been licensed in various countries, and their widespread use in universal mass vaccination programs is being implemented (55).Rotaviruses form a genus of the Reoviridae family. They contain a genome of 11 segments of double-stranded RNA (dsRNA) enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
252
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(263 citation statements)
references
References 59 publications
11
252
0
Order By: Relevance
“…Interestingly, all positive-strand viruses rely on lipids to replicate, mostly from the organelle membrane but sometimes from lipid droplets [27]. For example, lipid droplets play a key role in hepatitis C virus and rotavirus replication [28,29]. Thus, DcPV may use lipid droplets in a similar way to replicate in the ladybeetle nervous tissues.…”
Section: Results and Discussion (A) The Bodyguard Behaviour: A Neurolmentioning
confidence: 99%
“…Interestingly, all positive-strand viruses rely on lipids to replicate, mostly from the organelle membrane but sometimes from lipid droplets [27]. For example, lipid droplets play a key role in hepatitis C virus and rotavirus replication [28,29]. Thus, DcPV may use lipid droplets in a similar way to replicate in the ladybeetle nervous tissues.…”
Section: Results and Discussion (A) The Bodyguard Behaviour: A Neurolmentioning
confidence: 99%
“…For example, cholesterol depletion by lovastatin, an inhibitor of cholesterol biosynthesis, was shown to reduce rotavirus replication in MA104 cells (31). Likewise, drugs that disperse lipid droplets by promoting lipolysis were shown to interfere with rotavirus particle or viroplasm formation (7). Therefore, lipid metabolism was suggested as a novel therapeutic target for rotavirus infections.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was shown that disruption of lipid rafts and/or lipid droplets decreased infectious rotaviruses by inhibition of rotavirus morphogenesis (7,10). Lipid rafts are specialized membrane domains enriched in glycosphingolipids, cholesterol, and protein.…”
mentioning
confidence: 99%
“…Rotaviruses associate with cellular lipid droplets for replication, and compounds disrupting lipid droplets inhibit rotavirus replication (39). Replication of another flavivirus, West Nile virus (WNV), is associated with intracellular membrane rearrangements and requires fatty acid synthesis (40).…”
Section: Discussionmentioning
confidence: 99%